Derivatives and development : a political economy of global finance, farming, and poverty. - Breger Bush, Sasha (Palgrave Macmillan, 2012)
An analysis of an increasingly popular set of policy proposals coming from international development organizations and non-profits which suggest that developing country farmers should be hedging their considerable exposure to price risk on derivatives markets thereby securing their incomes from the vagaries of global commodity markets. Derivatives and Development is an analysis of an increasingly popular set of policy proposals coming from international development organizations and non-profits which suggest that developing country farmers should be hedging their considerable exposure to price risk on derivatives markets (futures and options markets), thereby securing their incomes from the vagaries of global commodity markets. It systematically and critically analyzes derivatives-based price risk management and the implications of derivatives advocacy for farmers. The author focuses upon small farmers in the Global South, a global community that currently numbers over one billion people. Small farmers in the Global South are among those groups most likely to be poor today, and are historically among those most at risk when agricultural markets are liberalized.